Scyllaridae Latreille 1825 ... - Alves, Maria De Lourdes; Ramos-Porto, Marilena; Viana, Girlene Fábia Segundo (Zenodo, 2008)
Family Scyllaridae Latreille, 1825 Parribacus antarcticus (Lund, 1793) Diagnosis: Melo, 1999:444, fig. 300. Previous records: Coelho and Ramos-Porto, 1998b: 387; Melo, 1999:444. Examined material: MAR/93: Ilha Rata, 1 female (ovigerous). Habitat: collected in the depth 12 m. Observation: medium brown yellow coloration. ... : Published as part of Alves, Maria De Lourdes, Ramos-Porto, Marilena & Viana, Girlene Fábia Segundo, 2008, Checklist of the Decapods (Crustacea) from the Fernando de Noronha Archipelago, Brazil, pp. 43-68 in Zootaxa 1881 on page 53, DOI: 10.5281/zenodo.184217 ...